Digital transformation, blockchain and music industry: a review from the performers' Collective Management Organizations (CMO) - Alberto Arenal; Cristina Armu\~na; Sergio Ramos; Claudio Feijoo; Juan Miguel Aguado-Terrón (International Telecommunications Society (ITS), 2023)
This paper study the challenges from the digital transformation of the music industry and the potential role of blockchain from the perspective of the Collective Management Organizations (CMO). Building on desk research and primary data from 9 semi-structured surveys with C level executives, this empirical analysis identifies main projects, their state of development and perspectives for this technology in music industry. Findings conclude that there are a limited number of blockchain projects led and/or with relevant participation of CMO and most of them are just research, proof of concept or pilots, far from a massive commercial phase. In addition, blockchain is not a priority for CMO and its adoption is not a priority in the digital transformation of this companies. The low quality of the data in the origin and the potential governance issues among different stakeholders within music industry appear as the main barriers for blockchain to be considered as a global solution. Ultimately, results in the paper provide a snapshot about the current state and future curve of adoption of blockchain as a solution to manage intellectual property rights in music industry.
Keywords: 330; digital music ecosystem; digital transformation; blockchain; Collective Management Organization; CMO